REVIEW OF MEDICAL PHYSIOLOGY - William F. Ganong, MD, Jack and DeLoris Lange Professor of Physiology (Lange Medical Books/McGraw-Hill Medical Publis, 2003)
This book is designed to provide a concise summary of mammalian and, particularly, of human physiology that medical students and others can use by itself or can supplement with readings in other texts, monographs, and reviews. Pertinent aspects of general and comparative physiology are also included. Summaries of relevant anatomic considerations will be found in each section, but this book is written primarily for those who have some knowledge of anatomy, chemistry, and biochemistry. Examples from clinical medicine are given where pertinent to illustrate physiologic points. In many of the chapters, physicians desiring to use this book as a review will find short discussions of important symptoms produced by disordered function.